Confucianism, law, and democracy in contemporary Korea - Kim, Sungmoon (East Asian comparative ethics, politics and philosophy of law, 2015)
A collection of original essays developing a Confucian political and legal theory, focusing on South Korea, traditionally the most Confucian East Asian country in its legal, political, and cultural practices.